Neuroanthropology of shamanic trance: a case study with a ritual specialist from Mexico - Toriz, Hugo; Fagetti, Antonella; Terán-Pérez, Guadalupe; Mercadillo, Roberto E. (Frontiers in Psychology, 2024)
In Mexico, shamans are recognized for the gift of entering a deep trance that allows them to know the origin of the diseases and conflicts that afflict people. They commonly treat patients through limpias (cleansing) to extract negative elements sent by a witch, or that were "collected" in places that harbor "evil winds." We present a case study of an 81-year-old Mexican shaman who noticed her gift in childhood. Electroencephalographic recordings were made while the shaman performed three activities: reading cards to diagnose a patient and answer the questions he posed; limpia with chicken eggs, stones and bells to absorb adverse "things"; and the incorporation trance through which a deceased is believed to occupy the shaman's body to use it as a communication channel. Alpha activity was observed when concentrated, suggesting a hypnagogic-like state. Predominant beta and gamma oscillations were observed, suggesting a potential plastic phenomenon that modulates the assimilation of external and internal referents guiding temporal schemes for action, attention and the integration of mnemonic, sensory and imaginative elements. We use a neuroanthropological approach to understand shamanic trance as a biological potential of the human brain to induce nonordinary states of consciousness linked to cultural beliefs and practices.